2014
DOI: 10.1186/1472-6874-14-40
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of wealth quintile on modern contraceptive use and fertility: evidence from Malawian women

Abstract: BackgroundHigh fertility and wide inequality in wealth distribution are phenomenal problems in sub-Saharan Africa. Modern Contraceptives (MC) are useful for limiting fertility, but are not always easily accessible in Malawi. This study examines the gap in MC use and fertility between women in the richest and poorest Wealth Quintile (WQ).MethodsThe study was cross-sectional in design and utilized Malawi DHS dataset, 2010. It focused on women of reproductive age. The dependent variables are ever and current use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
75
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 15 publications
36
75
4
3
Order By: Relevance
“…Similar studies in Malawi and Ghana respectively have found a strong association between wealth quintile and modern contraceptive use 11,29 . A study in Malawi reported a significant difference in prevalence of modern contraceptive use of 82.4% among women of richest wealth quintile compared to 66.8% among the poorest.…”
Section: African Journal Of Reproductive Health September 2017; 21 (3supporting
confidence: 54%
See 3 more Smart Citations
“…Similar studies in Malawi and Ghana respectively have found a strong association between wealth quintile and modern contraceptive use 11,29 . A study in Malawi reported a significant difference in prevalence of modern contraceptive use of 82.4% among women of richest wealth quintile compared to 66.8% among the poorest.…”
Section: African Journal Of Reproductive Health September 2017; 21 (3supporting
confidence: 54%
“…A study in Malawi reported a significant difference in prevalence of modern contraceptive use of 82.4% among women of richest wealth quintile compared to 66.8% among the poorest. Women in the richest wealth quintile were more likely to ever use modern contraceptive (OR=2.36; CI=2.07-2.69, p<0.001) than the poorest 11 . This suggests that financial constraint probably plays a role in reduced contraceptive usage among poor women.…”
Section: African Journal Of Reproductive Health September 2017; 21 (3mentioning
confidence: 97%
See 2 more Smart Citations
“…According to the women interviewed, to be informed about how different contraceptive methods work and to have one's questions answered are both important components of contraceptive counselling. In undeveloped countries, household income was shown to have an effect on the use and choice of contraception method [21]. Both the prevalence of regular use of contraceptives and choice of modern contraceptives were higher among women with higher incomes.…”
Section: Discussionmentioning
confidence: 95%